2004
DOI: 10.1117/12.550100
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of localized surface plasmon fields via exposure of a photosensitive polymer

Abstract: We present a method for mapping the electromagnetic field distribution in the vicinity of noble metal nanoparticles able to sustain localised surface plasmon resonance (LSPR). The field distribution is coded by topographic change in a selfdeveloping photosensitive polymer (PMMA-DR1). Metallic nanostructures are fabricated by e-beam lithography and optically characterised by extinction spectroscopy. Photoinduced topographic changes are checked by means of atomic force microscopy (AFM). The dipolar character of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For azo‐dye functionalized polymers, irradiation induces a conformational change between the trans and the cis isomers of the azo‐group. As a consequence mass transport takes place which induces a pushing or pulling of the polymer, creating topographic modifications of the polymer film surface 13–15. These topographic features were recorded directly by atomic force microscopy without the need of an extra chemical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For azo‐dye functionalized polymers, irradiation induces a conformational change between the trans and the cis isomers of the azo‐group. As a consequence mass transport takes place which induces a pushing or pulling of the polymer, creating topographic modifications of the polymer film surface 13–15. These topographic features were recorded directly by atomic force microscopy without the need of an extra chemical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…That is why the optical near fields have been extensively studied during the last decades with respect to their numerous applications in fluorescence and Raman signal enhancement, chemo- and biosensing, and near field lithography. , A number of numerical methods that allow for calculation of plasmon modes and intensity distribution of the near field for nanoparticles of different geometries are available. Furthermore, high resolution techniques such as scanning near field optical microscopy , and single molecule imaging have been used for direct experimental visualization of the enhanced optical near fields (local distribution and intensity) of metal nanostructures. Alternative visualization techniques include imprinting the near field in a photosensitive polymer coating, , in the metal nanostructures themselves , or ablative reactions on silicon or glass, , that cause a topography change that reflects the intensity enhancement and can be imaged with Atomic Force Microscopy (AFM) or Scanning Electron Microscopy (SEM). All these results have shown that the optical near fields of metal particles decay on very small length scales and can be used to modify materials located in the nanometer proximity of the particles.…”
Section: Introductionmentioning
confidence: 99%